Asymmetric hydrogenation of TIPS-protected oximes with chiral boranes. Issue 18 (19th April 2022) - Yu, Kuai; Feng, Xiangqing; Du, Haifeng
Abstract : A chiral borane-catalyzed metal-free asymmetric hydrogenation of TIPS-protected oximes has been successfully realized to furnish the desired hydroxyamine derivatives without the N–O bond cleavage in high yields with moderate ees. Abstract : An enantioselective metal-free hydrogenation of TIPS-protected oximes has been successfully realized for the first time by using chiral borane catalysts derived from chiral dienes and Piers' borane. A variety of hydroxylamine derivatives were afforded in 84–99% yields with 33–68% ees.